2008
DOI: 10.1111/j.1442-9993.2008.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

A native dasyurid predator (common planigale, Planigale maculata) rapidly learns to avoid a toxic invader

Abstract: Interactions between invasive species and native fauna afford a unique opportunity to examine interspecific encounters as they first occur, without the complications introduced by coevolution. In northern Australia, the continuing invasion of the highly toxic cane toad Bufo marinus poses a threat to many frog-eating predators. Can predators learn to distinguish the novel toxic prey item from native prey (and thus, avoid being poisoned), or are longer-term genetically based changes to attack behaviour needed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 47 publications
5
70
0
Order By: Relevance
“…For example, the arboreal species Phascogale tapoatafa is difficult to detect and rarely trapped in the Northern Kimberley (Start et al 2007). Species that have restricted distributions in the Kimberley in general and were not detected on the islands include Mesembriomys gouldii, Conilurus penicillatus, Trichosurus vulpecula and Petropseudes dahli, the latter species being restricted to particular rocky habitat types (McKenzie et al 1975;Start et al 2007;Webb et al 2008). Tall open forests that contain hollow-bearing trees favoured by all these species (except P. dahli) (Friend et al 1991;Woinarski et al 1999) have a restricted distribution on the Kimberley islands, probably due to the mostly skeletal soils on the majority of the islands (Burbidge et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the arboreal species Phascogale tapoatafa is difficult to detect and rarely trapped in the Northern Kimberley (Start et al 2007). Species that have restricted distributions in the Kimberley in general and were not detected on the islands include Mesembriomys gouldii, Conilurus penicillatus, Trichosurus vulpecula and Petropseudes dahli, the latter species being restricted to particular rocky habitat types (McKenzie et al 1975;Start et al 2007;Webb et al 2008). Tall open forests that contain hollow-bearing trees favoured by all these species (except P. dahli) (Friend et al 1991;Woinarski et al 1999) have a restricted distribution on the Kimberley islands, probably due to the mostly skeletal soils on the majority of the islands (Burbidge et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, a captive study showed that S. virginiae and P. maculata learned to avoid Cane Toads after initial encounters (Webb et al 2008;Shine 2010), and S. virginiae abundance did not vary at sites colonised by Cane Toads in Kakadu National Park, Northern Territory (Shine 2010).…”
Section: Figurementioning
confidence: 94%
“…;mammals-Webb et al 2008). That aversion may reduce rates of predation on native anurans that superWcially resemble cane toads (Webb et al 2008). Other indirect eVects of toad invasion may include a reduction in the abundance of disease-carrying mosquitoes (Hagman and Shine 2007).…”
Section: Pairwise Comparisonsmentioning
confidence: 99%
“…If the predator does not receive a lethal dose of toxin, it may alter its future behaviour as a result of the encounter. For example, marsupial carnivores (Planigale maculata), fishes (Lates calcifera, Mogurnda mogurnda) and frogs (Litoria dahlii) can learn in this way: after attempting to eat toxic B. marinus tadpoles or metamorphs, the predators subsequently avoid this prey type (Crossland 2001;Nelson 2008;Webb et al 2008). Such effects might influence predator-prey relationships in tropical Australia, the home of a diverse frog fauna (Tyler 1999).…”
Section: Introductionmentioning
confidence: 99%